Studi Awal: Analisis Sifat Fisika Lemak Babi Hasil Ekstraksi Pada Produk Pangan Olahan - Muhammad Taufik; Desi Ardilla; Dafni Mawar Tarigan; Muhammad Thamrin; Mariany Razali; Muhammad Iqbal Afritario (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Technological advances and diversity of the meat processed have grown tremendously with exceptional quality and price. Often found pork fat mixed with other meat processed. This led many experts to find a simple and inexpensive method of examining the physical properties of pig fat. This research is a preliminary study in the analysis of fat physics properties of pigs that aims to analyze the physical properties of extraction Pigs on the meat processed. In this study, n-hexane was carried used variated of concentrations and sample weights respectively : 20% : 10 g, 30% : 20 g, 40% : 30 g, 50% : 40 g. Specific gravity is obtained respectively 0.8208, 0.8210, 0.8215, 0.8215. The refractive index was obtained respectively 1.502, 1.502, 1.503, 1.505. The melting point was obtained respectively 42,638, 42,700, 42,700, 42,700. Iodine numbers were obtained respectively 46,441, 46,449, 46,460, 46,463 and the saponification numbers were obtained respectively 228,446, 228,440, 228,435, 228,428